Peningkatan Literasi Ekonomi Tentang Audit Keuangan bagi Siswa SMP Negeri 9 Kota Sibolga - Simamora, Fauziah Nur; Siregar, Ali Nurdin; Harahap, Eli Marlina (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2024)
SMP Negeri 9 is located in the Sibolga Sambas sub-district together with SMP Negeri 10 Sibolga. The students of SMP Negeri 9 Sibolga have studied economic subjects but with limited learning media and their implementation in daily life, students are still not efficient. The benefits of studying Economics for a person students can train someone in developing a student's creative ideas, train a student to be socially minded, more thorough and economical, train a student in setting the priority scale of needs from the most important needs. The aim of this PkM is to increase students' insight into Economics because studying economics trains a student to be more independent in managing his needs, learning how to fulfill a student's needs. Training a student's time and financial management and understanding a student's life needs. In training a student in developing creative ideas. All PkM participants, namely class IX students, PkM was held in August for 1 month and this PkM activity has resulted in an understanding of economics such as students being able to audit cash in class and can already think about choosing an accounting major when entering high school (SMA). later. Students will be able to practice and understand from themselves about financial reports and the parts of the economy.